Agility vs. Tradition: A Slovak Perspective on Modern Project Management - Banáš, Daniel; Hirtl, Martin; Hrablik Chovanová, Henrieta (Management and Production Engineering Review, 2026)
Agile Project Management (APM) is a widely adopted methodology, recognized for its adaptability, iterative delivery, and collaborative customer engagement. This study compares APM adoption in the Slovak Republic with global trends, utilizing empirical data from two surveys. The first survey comprises responses from 116 Slovak companies; the second draws data from the 17th State of Agile Report. The research assesses the extent of APM implementation in Slovakia, identifies key benefits, and investigates specific barriers to broader adoption. Findings reveal that while Slovak organizations report improvements in competitiveness, customer satisfaction, and delivery speed—consistent with global patterns—significant deficiencies persist in agile maturity, management support, and organizational culture alignment. These insights underscore the necessity for targeted investments in training, leadership engagement, and agile maturity assessment to fully leverage APM's potential within the Slovak business environment.